Seeing the better city : how to explore, observe, and improve urban space - Wolfe, Charles R. (Washington : Island Press, 2016)
"In order to understand and improve cities today, personal observation remains as important as ever. While big data, digital mapping, and simulated cityscapes are valuable tools for understanding urban space, using them without on-the-ground, human impressions risks creating places that do not reflect authentic local context. Seeing the Better City brings our attention back to the real world right in front of us, focusing it once more on the sights, sounds, and experiences of place in order to craft policies, plans, and regulations to shape better urban environments." --Publisher .
Introduction: Why Urban Observation Matters: Seeing the Better City -- 1. How to See City Basics and Universal Patterns -- 2. Observational Approaches -- 3. Seeing the City through urban Diaries -- 4. Documenting Our Personal Cities -- 5. From Urban Diaries to Policies, Plans, and Politics -- Conclusion: What the Better City Can Be.
Includes bibliographical references (pages 183-209) and index.
Keywords: City planning; ARCHITECTURE / Sustainability & Green Design; ARCHITECTURE / Urban & Land Use Planning; City planning